Effect of Webbing Angle on Tensile and Bending Strengths in Human Hair Fiber Reinforced Composites - Paundra, Fajar (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
Composite is a combination of two or more materials that have different basic properties. This study aims to analyze the effect of woven angle on hair fiber composites on tensile and bending strength. The composite is composed of polyester resin and human hair waste. Hair was soaked in 5% NaOH solution for 1 hour and woven with angle orientation 0°/90°, 15°/105°, 30°/120° and 45°/135°. The process of making composites is made by the Compression Molding method for 24 hours. After making the composite, a density test was carried out with the ASTM C271 standard, tensile test with ASTM D3039 standard and bending test with the ISO 178 standard. The results of the density test obtained an increase in the density value with the lowest density value of 0.82 g/ml and the highest 0.85 g/ ml to produce a lighter composite. Then the tensile test results show the highest tensile strength value of 16.47 MPa which occurs at an angle of 0°/90°. The results of the bending test obtained an increase in bending strength with the highest bending strength value of 47.1 MPa which occurred at an angle of 0°/90°.